1989
DOI: 10.4319/lo.1989.34.2.0478
|View full text |Cite
|
Sign up to set email alerts
|

Organic nitrogen mineralization and substrate limitation of bacteria in Lake Michigan

Abstract: Labile organic nitrogen mineralization and the apparent degree of bacterial substrate limitation were examined to consider seasonal relationships between substrate availability and bacterial activity in Lake Michigan. Accumulation rates of ammonium nitrogen in amino acid fortified and unfortified samples of epilimnetic Lake Michigan water, incubated in the dark, provided reasonable estimates of potential and actual rates of organic nitrogen mineralization. The labile organic nitrogen demand (LOND), defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…Applying the average bacterial cell C content, determined from 1986 data, to bacterial sizes and concentrations determined in the July 1985 experiment yielded similar results: C consumption of 120, 132, 192, and 213 pg C liter-' from 5-, 28-, 70-, and 95-m water. Our overall results of decreasing LDOC concentration during summer-indicating that demand is greater than supply at that time-are consistent with another recent study from the same region in Lake Michigan which demonstrated that bacteria are more substrate limited in summer than in spring (Gardner et al 1989). Higher LDOC concentrations in the deep region from our study (Table 1, Fig.…”
Section: 1; Two-tailed T-test)supporting
confidence: 81%
“…Applying the average bacterial cell C content, determined from 1986 data, to bacterial sizes and concentrations determined in the July 1985 experiment yielded similar results: C consumption of 120, 132, 192, and 213 pg C liter-' from 5-, 28-, 70-, and 95-m water. Our overall results of decreasing LDOC concentration during summer-indicating that demand is greater than supply at that time-are consistent with another recent study from the same region in Lake Michigan which demonstrated that bacteria are more substrate limited in summer than in spring (Gardner et al 1989). Higher LDOC concentrations in the deep region from our study (Table 1, Fig.…”
Section: 1; Two-tailed T-test)supporting
confidence: 81%
“…The dissolved nutrients being taken up metabolically from the solution by phytoplankton aggregate into organic particles, and organisms can be decomposed into inorganic nutrients through the mineralization process (Halemejko and Chrost 1984). However, the effects of the mineralization process are estimated to be small and it was generally not taken into consideration in the nutrient limitation bioassays (Bloesch et al 1977;Gao et al 2000Gao et al , 2006Gardner et al 1989;Kagami et al 2013;Kim et al 2006;Kolzau et al 2014). In this case, a particular nutrient could limit the growth of the phytoplankton once its concentration declined to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Mississippi River plume region, about 90% of the 'assimilated' I5N that had been added as labeled amino acids was recovered as 15NH4+ in bottle experiments with dark subsurface waters as compared to about 48% in surface waters under natural light . Similarly, organic substrate-depleted Lake Michigan bacteria regenerated an amount of ammonium approximately equivalent to the amount of added DFAA consumed (Gardner et al 1987(Gardner et al , 1989. Conversely, if other sources of labile carbon are available to be metabolized, more of the amino-N can be incorporated into biomass (see 'Results').…”
Section: Methodsmentioning
confidence: 99%